2019
DOI: 10.2196/12007
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Patient Experience Data on Health Systems’ Websites and Commercial Physician-Rating Websites: Mixed-Methods Analysis

Abstract: Background Some hospitals’ and health systems’ websites report physician-level ratings and comments drawn from the Consumer Assessment of Healthcare Providers and Systems surveys. Objective The aim was to examine the prevalence and content of health system websites reporting these data and compare narratives from these sites to narratives from commercial physician-rating sites. Methods We identified health system websites active between June … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Lagu et al [14] found that 88% of ratings were positive for both generalists and specialists (as defined by a rating of 3 or greater on a 4-point scale). A prior study also demonstrated that most comments on PRWs are positive [15]. Generally, our findings are consistent with these prior investigations suggesting that most ratings are either excellent or poor [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lagu et al [14] found that 88% of ratings were positive for both generalists and specialists (as defined by a rating of 3 or greater on a 4-point scale). A prior study also demonstrated that most comments on PRWs are positive [15]. Generally, our findings are consistent with these prior investigations suggesting that most ratings are either excellent or poor [16].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, social media presence, such as Facebook followers, has been shown to correlate with US News and World Report reputation score [29]. Finally, utilizing noncommercial PRWs can also be valuable because the percentage of positive comments has been shown to be higher on health systems’ online review websites when compared to commercial PRWs [15].…”
Section: Discussionmentioning
confidence: 99%
“…Patients' and their families' needs, values, and inputs influence care decisions [1]. Patients are researching treatments on the internet and engaging as advocates and even as partners with physicians both on the internet and in person [1][2][3][4][5]. A crucial aspect of patient experience is the patient-clinician engagement or using a relationship-centered care approach.…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest growing frustration with online reporting of quality and experience data because of the rapidly changing landscape, with recent increases in the presence of patientgenerated reviews 8,11 and the emergence of a new phenomenon in which hospitals and health systems have begun to publish physician-specific patient experience data and patient comments on their websites, for example. 25 However, this finding may also merely reflect that this sample is different than previously surveyed populations. Physicians' skepticism towards commercial physician rating sites has also been previously reported.…”
Section: Discussionmentioning
confidence: 75%